Pengukuran Islamicity Performance Index (IPI) Pada Kinerja Keuangan Bank Central Asia (BCA) Syariah Periode 2017-2021 - Chandra Ayu Nurfallah; Assyifa Nurtiasih; Suchehi Nur Diawati; Mirta Ulfah Rufi Widya Janah; Haura Sabita Putri (Academica: Journal of Multidisciplinary Studies, 2022)
Assets of Islamic financial institutions always increase from year to year. One of those that experienced an increase was Bank Central Asia (BCA) Syariah which experienced an increase of 9.5% in 2021 from the previous year with a nominal figure of 10,642.3 billion. There is a lot of general discussion in the community that Islamic banks are not much different from conventional banks. Some even think they have the same principle. Thus, this research needs to be done to determine the compliance of Islamic principles in BCA Syariah. This measurement is carried out using the Islamicity Performance Index (IPI) proposed by Hameed (2004). The research was conducted using quantitative methods with a descriptive approach. The results showed that the PSR and IIC ratios had the predicate "quite satisfactory" and "very satisfactory." Meanwhile, the EDR ratio and zakat performance are inversely proportional to the "very unsatisfactory" predicate. The DEWR ratio shows a gap between directors and employees 21-29 times during 2017-2021. This research can contribute to all stakeholders in BCA Syariah. Keywords: BCA Syariah; Islamicity Performance Index; Sharia financial performance.